A novel approach to monitor clearance of host cell proteins associated with monoclonal antibodies. (26th July 2014) - Aboulaich, Nabila; Chung, Wai Keen; Thompson, Jenny Heidbrink; Larkin, Christopher; Robbins, David; Zhu, Min
<x xml:space="preserve">Abstract</x> Co‐purification of a subset of host cell proteins (HCPs) with monoclonal antibodies (mAbs) during the capture of mAbs on Protein A affinity chromatography is primarily caused by interactions of HCPs with the mAbs. To date, there is limited information about the identity of those HCPs due to the difficulty in detecting low abundance HCPs in the presence of a large amount of the mAb. Here, an approach is presented that allows identification of HCPs that specifically associate with the mAb, while avoiding interference from the mAb itself. This approach involves immobilization of purified mAb onto chromatography resin via cross‐linking, followed by incubation with HCPs obtained from supernatant of non‐mAb producer cells that are representative of the expression systems used in mAb manufacturing. The HCPs that bind to the mAb are recovered and identified using mass spectrometry. This approach has not only allowed a comprehensive comparison of HCP subpopulations that associate with different mAbs, but also enabled monitoring of the effects of a variety of wash modifiers on the dissociation of individual HCP–mAb interactions. The dissociation of HCPs that associated with the mAb was monitored by enzyme‐linked immunosorbent assay and mass spectrometry. This approach can be utilized as a screening tool to assist the development of effective and targeted wash steps in Protein A chromatography that ensures not only reduction of HCP levels copurified with the mAb but also removal of specific HCPs that may have a potential impact on mAb structural stability and patient safety. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1114–1124, 2014